2011
DOI: 10.1007/s00436-011-2511-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorescent lectin binding to distinguish Teladorsagia circumcincta and Haemonchus contortus eggs, third-stage larvae and adult worms

Abstract: Lectin binding to carbohydrates on parasite surfaces has been investigated as a method of distinguishing adult worms, eggs and sheathed and exsheathed L3 of Teladorsagia circumcincta and Haemonchus contortus, economically important abomasal parasites in temperate climates. Both species were maintained as pure laboratory cultures of field isolates from New Zealand. Each of the four life cycle stages could be distinguished by the binding of at least one lectin: adult worms by Sambucus nigra agglutinin (SNA); egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Therefore, the ricin protein, a toxic protein with 60 kDa which is contained in R. communis seeds (WORBS et al, 2011), cannot be the active compound against H. contortus eggs, although it is known that the surface of H. contortus eggshells contains galactose carbohydrate (PALMER; McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012), which is a binding site for ricin. Trypsin inhibitor activity, albeit weak, was also observed in the CERN fraction of R. communis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ricin protein, a toxic protein with 60 kDa which is contained in R. communis seeds (WORBS et al, 2011), cannot be the active compound against H. contortus eggs, although it is known that the surface of H. contortus eggshells contains galactose carbohydrate (PALMER; McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012), which is a binding site for ricin. Trypsin inhibitor activity, albeit weak, was also observed in the CERN fraction of R. communis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the presence of carbohydrates on GIN surfaces, using labeled lectins (BONE;BOTTJER, 1985;PALMER;McCOMBE, 1996;JURASEK et al, 2010;HILLRICHS et al, 2012). In these studies, Concanavalin A (ConA), Lens culinaris agglutinin (LCA), Maclura pomifera agglutinin (MPA), peanut agglutinin (PNA) and Pisum sativum agglutinin (PSA) were bound to the egg surfaces, suggesting the presence of glucose, mannose and galactose carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…a2,3-linked sialic acids were detected using MALII, a2,6-linked sialic acids by SNA-I, exposure of terminal (b-)galactose/T antigen by PNA, exposure of terminal (a-)galactose and (a-)GalNAc by GSL-I, (poly) GlcNAc (chitobiose) by WGA, and (a-)fucose by AAL (30)(31)(32). Free lectin was removed by washing the cells in carbofree blocking solution, and cell-bound biotinylated lectin was conjugated with 2 mg/mL streptavidin-phycoerythrin for 15 minutes (33).…”
Section: Lectin Staining and Flow Cytometrymentioning
confidence: 99%
“…V. anguillarum) via a galactose or lactose sugar unit, whereas Con-P recognizes oligo-mannose sugars via allosteric regulation. Actually, some mannose-specific lectins bind strongly to parasitic nematodes and nematode eggs (18). Furthermore, Con-P was detected and cloned from the peritoneal cells and the cells that encapsulated parasitic nematodes in the abdominal cavity (24), and Con-P interacted with yeast mannan (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%